2021
DOI: 10.1029/2020jf006060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changing Concavity Indices on Channel Steepness and Divide Migration Metrics

Abstract: Impact of changing concavity indices on channel steepness and divide migration metrics

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Although θ ref optimizations in individual catchments are, collectively, consistent with the regional analysis, they suggest substantial intercatchment variability. If true, then this would complicate topographic analyses and potentially confound efforts to evaluate relationships between erosion and topography ( 29 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although θ ref optimizations in individual catchments are, collectively, consistent with the regional analysis, they suggest substantial intercatchment variability. If true, then this would complicate topographic analyses and potentially confound efforts to evaluate relationships between erosion and topography ( 29 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…River profile collinearity in χ-elevation plots (χ- z ) has become a popular method to determine optimal θ ref values from topography ( 34 , 36 , 37 ). This method leverages the SPM prediction that, provided θ ref is set appropriately, the χ-transform linearizes river profiles adjusted to uniform conditions with slopes equal to k sn ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…While varying m and n, we maintain their ratio constant at 0.45, a widely applied average channel concavity (e.g., Wobus et al, 2006;Harel et al, 2016), and in line with the global average of 0.42 reported by Gailleton et al (2021).…”
Section: Methodsmentioning
confidence: 89%
“…At more restricted scales, erosion rates based on cosmogenic nuclides (e.g., 10 Be) show a modest exponential correlation with catchment-averaged slope, as does normalised steepness in stream profiles (Portenga and Bierman, 2011;Harel et al, 2016). Nevertheless, it is widely observed that steepness and stream power parameters are subject to notable variation wherever climate and/or lithology differ (Harel et al, 2016;Gailleton et al, 2021;Marder and Gallen, 2022), and a robust analysis must accommodate such interactions.…”
Section: Introductionmentioning
confidence: 99%
“…At the catchment-scale, diversity in river morphology has been observed in the Philippines with eight distinct River Styles (geomorphic river types) identified in the 586 km 2 Bislak catchment [40]. Spatial heterogeneity in the concavity index, used to indicate how quickly river channel gradient declines downstream, has been shown across the Cordillera Central of Ilocos Norte [69]. Physical attributes of the landscape impose boundary conditions that control hydromorphological attributes in river systems; the heterogeneity in morphometric and topographic characteristics are likely explained by the diverse geologic, tectonic and climatic settings across the analysed catchments.…”
Section: Diversity and Distinctiveness Of Stream Network And River Ca...mentioning
confidence: 99%